Shelf life study of handmade and industrially processed Minas frescal cheese - Silva, Thamiris Evangelista; Santos, Priscila Alonso dos; Silva, Thamara Evangelista; Silva, Kamilla Soares [UNESP]; Machado, André Luiz Borges; Garcia, Lismaíra Gonçalves Caixeta (Emerald, 2019)
Purpose: The purpose of this study is to characterize and compare the results of the inspection mark of handmade and industrially processed Minas frescal cheese. It is one of the most commonly made and consumed cheeses in Brazil, and its production processes range from handmade cheeses produced in small household production sites to cheeses manufactured in large dairy factories subject to federal inspection. Design/methodology/approach: The samples were stored for 10 days at 4°C in a biochemical oxygen demand chamber. Cheeses were analyzed using physicochemical analyzes, yield and syneresis indices and microbiological analyses. Findings: The cheese A met the criterion of regulatory classification for very high humidity (65.32 g/100 g), while cheese B did not meet the criterion (54.38 g/100 g). Cheeses A (19.01 g/100 g) and B (24 g/100 g) showed average fat contents that did not comply with current legislation. The most probable number per g of thermotolerant coliforms was outside the acceptable range (>24 × 102 MPN/g), and Salmonella spp. were present in the tested samples. The highest yield was observed for handmade cheese (an average of 5.35 L of milk to produce 1 kg of cheese), which had the highest syneresis during the storage period (p = 0.004), reaching 14.26% on the 10th day of storage. Originality/value: Municipal and state inspection certificates do not ensure the microbiological quality of Minas frescal cheese, indicating flaws in the good manufacturing practices and/or in the milk pasteurisation stage.
Keywords: Characteristic; Milk; Processing; Quality; Storage